(untitled) (Castilla. Estudios de Literatura, 2020)
This article presents the procedure to be followed in a Spanish edition of the correspondence between Schiller and Goethe. After distinguishing between critical editing and comment-editing, it is specifically about how letters are edited. Subsequently, it is assessed how these are both "window" to the thought of an author, as a document of his time. This gives rise to a revision of the critical edition of 2009. After this tour it is concluded that the edition of authors far from us in time, can not do without intermediate readings and must be a comment-editing.